Ответы и объяснения

Лучший Ответ!
2012-05-27T00:12:44+04:00

cosx=2 √2

x-π/4 +2πn, где n∈ z

 

2cosx= -√3

x=-√3/2

x=(π-π/6) +2πn,n∈z

x=5π/6+2πn,n∈z

 

√2cosx-1=0

√2cosx=1

cosx=1/√2

x=π/4 +2πn,n∈z

 

sin2x=√2/2

2x=(-1)^k × π/4,n∈z

x=(-1)^k × π/8,n∈z

 

 

cos x/3 =-1/2

x/3=(π-π/4)+2πn,n∈z

x/3=3π/4+2πn,n∈z

x=9π/4+6πn,n∈z

 

 

cos4x=0

4x=π/2+πn,n∈z

x=π/8+πn/4,n∈z

 

cos(π/6-2x)=0

π/6-2x=π/2+πn,n∈z

-2x=π/2-π/6+πn,n∈z

-2x=π/3+πn,n∈z

x=-π/6-πn/2,n∈z

 

2six²x+sinx-1=0

Пусть sinx=t, t∈[-1;1]

2t²+t-1=0

D=1+8=9

t₁=(-1+3)/2=1

t₂=(-1-3)/2=-2(∉)

 

sinx=1                

x=π/2+2πn,n∈z

 

остальные аналогично